False-Negative Results of Endoscopic Biopsy in the Diagnosis of Gastrointestinal Kaposi's Sarcoma in HIV-Infected Patients. (26th November 2012) - Nagata, Naoyoshi; Sekine, Katsunori; Igari, Toru; Hamada, Yohei; Yazaki, Hirohisa; Ohmagari, Norio; Akiyama, Junichi; Shimbo, Takuro; Teruya, Katsuji; Oka, Shinichi; Uemura, Naomi
Abstract : Kaposi's sarcoma (KS) is a rare endothelial neoplasm mainly involving the skin, but it is often associated with AIDS. Diagnosis of gastrointestinal (GI) tract KS, a common site of visceral involvement in AIDS, is important, but endoscopic biopsy carries a risk of false-negative results (FNRs) due to its submucosal appearance. This study sought to determine the rate and causes of FNR for endoscopic biopsy of GI-KS lesions. Endoscopic biopsy samples of 116 GI-KS lesions were reviewed retrospectively. All GI-KS lesions were confirmed to be resolved following KS therapy. FNRs were yielded for 41 of the lesions (35.3%). Among upper and lower GI sites, the esophagus was the only site significantly associated with FNRs (P < 0.01 ). Small size (<10 mm) and patches found on endoscopy were significantly associated with FNRs (P < 0.05 ). Findings of submucosal tumor (SMT) with ulceration were significantly associated with true-positive results (P < 0.05 ). In conclusion, FNRs were found in 35.3% of GI-KS lesions and were especially related to the site of the esophagus and endoscopic early stage (small size or patch appearance). An SMT with ulceration may be relatively easy to diagnose on endoscopic biopsy. Caution should be exercised when performing endoscopic biopsy of these lesions in AIDS patients and evaluating the histological features.